FinTech and the Development of Crowdfunding Models in Indonesia - Abdullah, Gailan Ismael (Indonesian Journal of Law and Economics Review, 2025)
General Background: Crowdfunding has become an essential alternative financing mechanism worldwide, particularly in emerging economies. Specific Background: In Indonesia, the rapid growth of digital platforms and financial technology (FinTech) provides opportunities to expand financial inclusion, yet challenges persist regarding regulation, trust, and operational efficiency. Knowledge Gap: Despite global research, little is known about how FinTech innovations specifically shape crowdfunding ecosystems in developing contexts like Indonesia. Aims: This study investigates the role of FinTech in enabling innovative crowdfunding models and examines their sustainability. Results: Using a mixed-methods approach with surveys (n=176), interviews (n=33), and case studies, the findings reveal that platform design, operational efficiency, and regulatory support significantly enhance trust and platform credibility, which in turn promote sustainability. Novelty: The study offers a comprehensive framework linking FinTech-driven design features, institutional backing, and user trust to the long-term viability of crowdfunding models. Implications: These insights advance academic understanding and provide practical guidance for policymakers, entrepreneurs, and investors to foster credible, inclusive, and sustainable crowdfunding systems in Indonesia. Highlights: FinTech strengthens crowdfunding through design, efficiency, and regulation. Trust and credibility are central to platform sustainability. Findings guide policymakers, entrepreneurs, and investors in emerging markets. Keywords: FinTech, Crowdfunding, Financial Inclusion, P2P Lending, Financial Innovation.